Pengaruh adversity quotient terhadap kemampuan metakognitif siswa kelas x SMKN Kebonagung - Lestari, Yuvendri Dwi (Program Studi Pendidikan matematika STKIP PGRI Pacitan STKIP PGRI Pacitan, 2024)
This study aims to determine the effect of the adversity quotient (high, medium, and low) on students' metacognitive abilities. This is an ex post facto study with a quantitative approach. The sample for this study was 76 students in class X of Kebonagung State Vocational School, taken with the Simple Random Sampling technique. Data collection techniques in this study use questionnaires and tests. Questionnaires are used to measure students' adversity quotients, and tests are used to measure metacognitive abilities on trigonometric material. The data analysis technique in this study uses a non-parametric test, namely the Kuskall-Wallis H. Based on the calculation results using a non-parametric test (Kuskall Wallis H) and obtaining sig. = 0.329> = 0.05, then is accepted. This means that there is no difference between adversity quotient (high, low, low) and students' metacognitive abilities. whereas based on then is accepted. This means that there is no difference between adversity quotient (high, low, low) and students' metacognitive abilities. This shows that adversity quotient (high, medium, low) has no effect or effect on students' metacognitive abilities.